KINERJA DAN PROSPEK PEMASARAN KOMODITAS MANGGA (Studi kasus petani mangga di Propinsi Jawa Barat) - ADE SUPRIATNA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
This study was conducted in 2005 and took place in West Java. The objectives ofstudy were (a) to identify characteristics of farmers and mango cultivation practice, (b) toanalyze the economical visibility of mango farm, (c) to describe the marketing channels andthe manner of each institution, and (d) to analyze the marketing margin and farmers share.The results showed that based on partial analysis, mango farm spent cost of Rp.6.4 million,gave farm return of Rp.30.1 million and farm benefit of Rp.23.6 million per hectare per year.The mango farm was suitable economically with R/C ratio of 4.64. In farm level, mango wasclassified into two grades, namely grade A/B (70%) and non grade (30%) which was namedgrade C (rucahan). For West Java area, grade A/B was marketed through three channels,namely (1) farmer ? collection trader ? agent ? central market ? traditional market ?consumer, (2) farmer ? collection trader ? agent ? central market ? shop/mangostand ?consumer, (3) farmer ? collection trader ? agent ? central market ? supplier ? supermarket ? consumer. While non grade (C) was marketed through one channel, namely farmer? collection trader ? agent ? local traditional market ? consumer. The farmers faced astructure of imperfect competitive market with some indicators such as a lot of seller and alittle of buyer, farmer’s marketing information was low, and the mango price was determinedby buyer. The central market took place as a referee market; the mango price offered bycentral market would be an arithmetical standard to determine the purchasing price byformerly institutions until the farmer level. In marketing grade A/B, agent reached a highestmargin, namely Rp.2, 500,-. They spent a highest cost of marketing and took a higher riskcaused by fluctuation of price. The third channel was longest channel and took a farmersshare of 29.4 percent. While the first and second channels were shorter than that of the thirdone and they took the farmers share of 41, 7 and 40.0 percent, respectively.